Sephadex-binding RNA ligands: rapid affinity purification of RNA from complex RNA mixtures - Srisawat, Chatchawan (Oxford University Press, 2001)
Sephadex-binding RNA ligands (aptamers) were obtained through in vitro selection. They could be classified into two groups based on their consensus sequences and the aptamers from both groups showed strong binding to Sephadex G-100. One of the highest affinity aptamers, D8, was chosen for further characterization. Aptamer D8 bound to dextran B512, the soluble base material of Sephadex, but not to isomaltose, isomaltotriose and isomaltotetraose, suggesting that its optimal binding site might consist of more than four glucose residues linked via α-1,6 linkages. The aptamer was very specific to the Sephadex matrix and did not bind appreciably to other supporting matrices, such as Sepharose, Sephacryl, cellulose or pustulan. Using Sephadex G-100, the aptamer could be purified from a complex mixture of cellular RNA, giving an enrichment of at least 60 000-fold, compared with a non-specific control RNA. These RNA aptamers can be used as affinity tags for RNAs or RNA subunits of ribonucleoproteins to allow rapid purification from complex mixtures of RNA using only Sephadex.